Effect of vibration dampers on the dynamic state of a drill string - Svitlytskyi, Viktor; Iagodovskyi, Sergii; Bilenko, Nataliia (Technology audit and production reserves, 2023)
The object of research is the drill string bottom structure using the correcting devices of drilling modes to control the dynamics of the drill string. The work is aimed at the study of longitudinal, torsional and transverse oscillations when adjusting the axial load on the bit by using a drilling shock absorber with a two-link characteristic. A dynamic model of the drill string during the drilling process is presented, which is a concentrated-continuous nonlinear system that interacts with the ball bit and the downhole engine as a source of energy. It is shown that elastic oscillations of all types affect the interaction of the bit with the outcrop rock. In order to evaluate drilling performance, it is necessary to take into account not only longitudinal, torsional and transverse oscillations, but also parametric oscillations, which are associated with the deformation of the weighted drill pipe under axial loads and during its rotation in the process of deepening the hole. It was found that transverse vibrations of weighted drill pipes, as a flexible element, during the drilling process are, as a rule, parametric in nature. They lead to the appearance of additional stresses in the elements of the column and, as a result, to the acceleration of their destruction and accelerated wear of the bit arms and rolling bearings. It is proved that in the future, for the development of dynamic models, it is necessary to take into account their hydrodynamics and the type, design and parameters of the applied punching elements. The obtained research results can be applied in practice in the process of designing the structure of the drill string bottom structure (DSBS) using correcting devices of drilling modes to control the dynamics of the drill string, by using a drilling shock absorber with a two-link characteristic in order to correct the axial load on the bit.